color(red)("First,")First, what you want to do is square both sides of the equation to get rid of the square root, since squaring a number is the inverse of taking the square root of a number:
T^2 = (2pi)^2sqrt((L/g)^2)T2=(2π)2√(Lg)2
T^2=(2pi)^2 (L/g)T2=(2π)2(Lg)
color(blue)("Second,")second, we simplify the (2pi)^2(2π)2 part so it's easier to read. Remember, when you square something in parenthesis, you are squaring every single term inside:
T^2=4pi^2 (L/g)T2=4π2(Lg)
color(purple)("third,")third, multiply both sides by gg:
gxxT^2=4pi^2 (L/cancel"g")xxcancelg
gxxT^2=4pi^2L
color(maroon)("finally,") divide both sides by T^2 to get g by itself:
(gxxcancelT^2)/cancelT^2=(4pi^2L)/T^2
Thus, g is equal to:
g=(4pi^2L)/T^2